THE ORATIO AD SANCTOS ATTRIBUTED TO THE EMPEROR CONSTANTINE AND THE ORACLE AT DAPHNE - Hanson, R. P. C. (The journal of theological studies, 1973)
R. P. C. HANSON; THE ORATIO AD SANCTOS ATTRIBUTED TO THE EMPEROR CONSTANTINE AND THE ORACLE AT DAPHNE, The Journal of Theological Studies, Volume XXIV, Issue 2,